"Without Flinching": Facing up to Race in Liberal Italy. (28th January 2019) - Finaldi, Giuseppe; Baratieri, Daniela
Abstract : This article examines the development of racial discourses in Italy during the process of unification and in the following years with respect to some of the fundamental issues experienced by and facing the new nation. Anthropologists and criminologists proselytised the new "science" purporting to have discovered a novel hermeneutic for how Italy should be imagined, moulded and propelled into the future. In this article, the test case provided for how race was engaged within the Italy emerging out of the process of unification is that of the "Assabesi", six black inhabitants of the small tract of land Italy had acquired in Africa in 1869, who were brought to Italy and displayed at the 1884 National Exhibition held in Turin. As Italy embarked on a period of extended colonial expansion, the questions of race, otherness, citizenship and boundaries became ever more pressing. Through an examination of the vicissitudes and debates surrounding the Assabesi's sojourn in Italy, the article seeks to demonstrate that while racism was one option in how Italy's new black subjects could be categorised and eventually ruled, it always had to contend with powerful and sustained counter‐arguments.